The Alpha Human versus the Korean: Figuring the Human through Technoscientific Networks. Issue 4 (1st December 2018) - Jeon, Chihyung
Abstract: What does the human look like in South Korea? This article identifies two different figurations of the human in contemporary South Korea: the alpha human and the Korean. The alpha human is a human imagined, shaped, and circulated on the network of technosciences and media; it is embraced by technoscientific researchers, entrepreneurs, policy makers, and journalists. The alpha human's defining characteristic is the extended longevity, or even immortality, made possible by the developments in biomedicine, artificial intelligence, and robotics. On the other hand, the figure of the Korean is imagined to be going through a crisis of survival, as it is excluded or displaced from technoscientific as well as socioeconomic networks. It is represented by the indexes of fertility, inequality, and suicide, as well as reports of lived experiences of Koreans across generations. What does it mean to craft such a futuristic figure, or even a fantasy, of the immortally networked alpha human when the Korean is figured as experiencing dispossession and disparity? This article suggests that the alpha human is a decontextualized figure that can propose only technofuturistic escape but no vision for collective action.